Mechanisms Underlying the Effects of Lianhua Qingwen on Sepsis-Induced Acute Lung Injury: A Network Pharmacology Approach - Yang, Ruhao; Yang, Haizhen; Wei, Jie; Li, Wenqiang; Yue, Fang; Song, Yan; He, Xin; Hu, Ke (Frontiers in Pharmacology, 2021)
Background and purpose: Sepsis is a life-threatening condition associated with secondary multiple organ injury. Acute lung injury (ALI) caused by sepsis has high morbidity and mortality in critical care units. Lianhua Qingwen (LHQW) is a traditional Chinese medicine composing of 11 herbs and 2 medicinal minerals. LHQW exhibits anti-inflammatory activity and is effective in treating pneumonia. Our study aimed to evaluate the effect of LHQW on sepsis-induced ALI and its underlying mechanism. Materials and Methods: A network pharmacology approach was used to predict the bioactive components and effective targets of LHQW in treating ALI. We established ALI model C57/BL6 mice via an intraperitoneal injection of LPS and inhibited p53 expression by pifithrin-α, in order to validate the mechanism by which LHQW exerted protective role in ALI. Hematoxylin-eosin staining was conducted to assess the severity of lung injury. The severity of inflammation was evaluated based on MPO (myeloperoxidase) activity. TUNEL assay was employed to detect apoptotic cells. The levels of p53 and caspase-3 were tested by immunohistochemical staining and Western blotting. The expression levels of Bcl-2, Bax, cytochrome C and caspase-9 were detected by Western blotting. Results: A total of 80 genes were associated with LHQW in the treatment of ALI. After PPI network construction, 4 active components (quercetin, luteolin, kaempferol and wogonin) and 10 target genes (AKT1, TP 53, IL 6, VEGFA, TNF, JUN, STAT 3, MAPK 8, MAPK1 and EGF) were found to be essential for ALI treatment. GO and KEGG analyses indicated that apoptosis pathway was mainly involved in the LHQW-ALI network. Animal experiments showed that LHQW was able to attenuate LPS-induced ALI, and medium-dose LHQW exhibited the most prominent effect. LHQW could inhibit the overexpression of p53 induced by LPS and suppress p53-mediated intrinsic apoptotic pathways by decreasing the levels of Bax, caspase-3 and caspase-9, increasing the expression of Bcl-2, and attenuating the release of cytochrome C in ALI mice. Conclusion: This study reveals that LHQW may alleviate LPS-induced ALI via inhibiting p53-mediated intrinsic apoptosis pathways.